2009
DOI: 10.1354/vp.08-vp-0206-w-fl
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function and Morphology Are Altered in Cattle Infected with the Prion Disease Transmissible Mink Encephalopathy

Abstract: Abstract. Transmissible spongiform encephalopathies (TSEs) are a group of diseases that result in progressive and invariably fatal neurologic disease in both animals and humans. TSEs are characterized by the accumulation of an abnormal protease-resistant form of the prion protein in the central nervous system. Transmission of infectious TSEs is believed to occur via ingestion of prion protein-contaminated material. This material is also involved in the transmission of bovine spongiform encephalopathy (''mad co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
6
22
0
Order By: Relevance
“…Our previous work has also demonstrated that changes in retinal function are detectable months prior to other signs of disease in cattle infected with transmissible mink encephalopathy [24]. Similarly, results presented here demonstrate that changes in retinal function as demonstrated by electroretinogram, specifically prolongation of the b-wave implicit time, are detectable at least 5 months prior to when cattle developed unequivocal signs of disease and were euthanized.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our previous work has also demonstrated that changes in retinal function are detectable months prior to other signs of disease in cattle infected with transmissible mink encephalopathy [24]. Similarly, results presented here demonstrate that changes in retinal function as demonstrated by electroretinogram, specifically prolongation of the b-wave implicit time, are detectable at least 5 months prior to when cattle developed unequivocal signs of disease and were euthanized.…”
Section: Discussionsupporting
confidence: 83%
“…We used immunohistochemistry to assess any potential differences in these cell types in retinas from BSE-inoculated animals. Immunoreactivity for the alpha subunit of protein kinase-C (PKC-alpha) was used to examine the morphology of rod bipolar cells [24]. While we observed some subtle differences between samples, such as what appeared to be an increase of PKC-alpha immunoreactive processes in the retinas of animals inoculated with classical BSE, these differences were not sufficient for blinded investigators to sort inoculated samples from control samples (data not shown).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As the retina has proven to offer diagnostic promise in TSEs [32], [33], two non-invasive tools were utilized to assess retinal changes during the incubation period. Retinal function and thickness were assessed through electroretinography and optical coherence tomography (OCT), respectively.…”
Section: Resultsmentioning
confidence: 99%